Glocalization of bioethics. Issue 1 (31st December 2022) - Bhakuni, Himani
ABSTRACT: There appears to be a conflict between global bioethical principles and the local understanding and application of these principles, but this conflict has misleadingly been characterized through the east–west dichotomy. This dichotomy portrays bioethical principles as western and as alien to non-western cultures. In this paper, I present reasons to reject the east–west dichotomy. Using the discussion around the principle of informed consent as an example, I propose that while bioethical values are common, bioethical governance must display a certain flexibility akin to Aristotle's metaphor about the Lesbian rule. Such flexibility combined with a deeper understanding of the lived experiences of bioethical subjects might lead to the purging of tensions between global and local, giving us Glocal Bioethics .